Mechanism of the toxicity induced by natural humic acid on human vascular endothelial cells. Issue 8 (8th October 2012) - Kihara, Yusuke; Yustiawati; Tanaka, Masato; Gumiri, Sulmin; Ardianor; Hosokawa, Toshiyuki; Tanaka, Shunitz; Saito, Takeshi; Kurasaki, Masaaki
<x xml:space="preserve">Abstract</x> Humic acid (HA), a group of high‐molecular weight organic compounds characterized by an ability to bind heavy metals, is normally found in natural water. Although the impairment of vascular endothelial cells in the presence of humic substances has been reported to be involved in some diseases, the mechanisms responsible for this involvement remain unclear. In this study, we examined the cytotoxicity of HA obtained from peatland in Central Kalimantan, Indonesia, to human vascular endothelial cells, as well as the mechanisms behind these effects. It was found that 50 mg/L HA showed cytotoxicity, which we considered to be mediated by apoptosis through the mitochondrial pathway because of an increase in the expression of caspases 6 and 9 in response to HA administration. In addition, this cytotoxicity was enhanced when cells in this experimental system were exposed to oxidative stress, while it was decreased by the addition of vitamin C. Thus, we conclude that the apoptosis induced by HA depends upon oxidative stress. Furthermore, an iron chelator, DFO, showed a tendency to decrease HA‐induced cytotoxicity, suggesting that iron may potentially mediate HA‐induced oxidative stress. In conclusion, long‐term consumption of HA‐rich water obtained from our study area may cause damage to endothelial cells and subsequent chronic health problems. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 916–925, 2014.